THE EFFECT OF VARIOUS TYPES OF NATURAL FEED ON THE GROWTH OF MANGROVE CRABS (Scylla serrata) IN TRADITIONAL POND FARMING - Tariska Putri Ramadani; Siti Komariyah; Andika Putriningtias (Universitas Teuku Umar, 2025)
The Mangrove Crab (Scylla Serrata) is one of the economically important fishery commodities that has delicious meat and high nutritional content. This study aims to obtain the best type of natural feed and analyze the effect of feeding various types of natural feed on the growth of mangrove crabs (Scylla Serrata) in traditional ponds. This study employed an experimental design using a Completely Randomized Design (CRD) with 4 treatments and 3 replications, comprising 12 units. The natural feed treatments were P1 (Rucah Fish), P2 (Chicken Intestines), P3 (Keongmas), and P4 (Rajungan), each at 5% of the diet. The study was analyzed using ANOVA with Excel and Duncan's multiple range test with SPSS. The study was conducted over 40 days in traditional ponds in Desa Lingkungan 3 Kampung Baru, Kelurahan Pangkalan Batu, Kecamatan Berandan Barat, Kabupaten Langkat. The results showed that the use of various types of natural feed did not have a significant effect (Fhit > Ftab) at a significance level of P > 0.01 on moulting percentage, absolute weight gain, daily specific growth rate, and survival rate (SR), but had a very significant effect (Fhit < Ftab) at the P < 0.01 significance level on the feed conversion ratio (FCR) of mangrove crabs (Scylla Serrata) in traditional ponds